Strategy Innovative Development Strategies for Success in Infrastructure Challenges at SDN Krian 2 Sidoarjo - Pamungkas, Dimas Dzakiy Wahyu; Anggraeni, Fitriya Helen; Sari, Fai'zah Dwi Kumala; Aminah, Siti; Wulandari, Ayu (Lembaga Yasin AlSys, 2024)
This research explores innovative strategies for holistic student development amidst limited infrastructure in a case study of SDN Krian 2 Sidoarjo. Despite facing challenges in the learning process such as limited classrooms, inadequate teaching materials and a lack of technological resources, this school has adopted creative methods to improve student success. Using a combination of qualitative methods, including observation, interviews with teachers, students and staff, and document analysis, this study identified the key strategies implemented by the school. These include developing student-centered learning approaches, optimizing available resources, community partnerships, and integrating collaborative and contextual learning. The findings highlight how good practices can bridge gaps in infrastructure, ensuring student growth in academic and non-academic areas. The results of this study provide valuable insights into effective school management practices that can be implemented in resource-constrained school.